Enhancing the diversity of self-replicating structures using active self-adapting mechanisms - Xu, Wenli; Wu, Chunrong; Peng, Qinglan; Lee, Jia; Xia, Yunni; Kawasaki, Shuji (Frontiers in Genetics, 2022)
A numerous variety of life forms has filled the earth through evolution. Evolution consists of two processes: self-replication and interaction with the physical environment and other living things around it. Initiated by~\citet{VonNeumann1966}, studies on self-replication in cellular automata have attracted many attentions, which aim to explore the logical mechanism underlying the replications of living things. In nature, competition is a common and spontaneous resource to drive the self-replications, whereas most cellular-automaton-based models merely focus on some self-protection mechanisms that may deprive the rights of other artificial life (loops) to live. Especially, \cite{Huang2013a} designed a self-adaptive self-replicating model using a greedy selection mechanism, which can increase the ability of loops to survive through occasionally abandoning part of their own structural information, for the sake of adapting to the restricted environment. Though this passive adaptation can improve diversity, it is always limited by the loop's original structure and unable to evolve or mutate new genes in a way that is consistent with the adaptive evolution of natural life~\citep{Miles2020,Moore2021,Monroe2022}. Furthermore, it is essential to implement more complex self-adaptive evolutionary mechanism not at the cost of increasing the complexity of cellular automata. To this end, this paper proposes new self-adaptive mechanisms, which can change the information of structural gene and actively adapt to the environment when the arm of a self-replicating loop encounters obstacles, thereby increasing the chance of replication. Meanwhile, our mechanisms can also actively add a proper orientation to the current construction arm for the sake of breaking through the deadlock situation. Our new mechanisms enable active self-adaptations in comparison with the passive mechanism in~\cite{Huang2013a}, which is achieved by including a few rules without increasing the number of cell states as compared to the latter. Experiments demonstrate that this active self-adaptability can bring more diversity than the previous mechanism, whereby it may facilitate the emergence of various levels in self-replicating structures.